1923
DOI: 10.1002/j.1537-2197.1923.tb05699.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Sand and Solution Cultures of Marquis Wheat

Abstract: The present study. in which a comparison is made of the growth of Marquis wheat in sand and solution cultures, represents one of several experiments involving solution III of the National Research Council series which are now in progress in the plant-physiology laboratory at Iowa State College.Most investigators attempting to determine the salt requirements of higher plants have used water cultures. Tottingham (2S) placed the whole proposition on a definite quantitative basis. He took the well-known Knop's sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1928
1928
1946
1946

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Hoagland (149, ISO) stated that roots of plants in solution cultures and sand cultures shift the hydrogen-ion concentration of the milieu rapidly toward neutrality. Bakke and Erdman (136) reported that the pH of their culture solutions changed during the growth of wheat from 3.75 to 5.95 in water cultures and to 6.66 in sand cultures. Robbins and Scott (128) determined the effect of different tissues upon the hydrogen-ion concentration of the solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoagland (149, ISO) stated that roots of plants in solution cultures and sand cultures shift the hydrogen-ion concentration of the milieu rapidly toward neutrality. Bakke and Erdman (136) reported that the pH of their culture solutions changed during the growth of wheat from 3.75 to 5.95 in water cultures and to 6.66 in sand cultures. Robbins and Scott (128) determined the effect of different tissues upon the hydrogen-ion concentration of the solution.…”
Section: Discussionmentioning
confidence: 99%
“…Bakke and Erdman (136) reported that the pH of their culture solutions changed during the growth of wheat from 3.75 to 5.95 in water cultures and to 6.66 in sand cultures. Hoagland (149, ISO) stated that roots of plants in solution cultures and sand cultures shift the hydrogen-ion concentration of the milieu rapidly toward neutrality.…”
mentioning
confidence: 99%